2016
DOI: 10.1534/genetics.115.186650
|View full text |Cite
|
Sign up to set email alerts
|

Is Continued Genetic Improvement of Livestock Sustainable?

Abstract: Large genetic improvements in the quantitative traits of growth, production, and efficiency of farmed livestock have been made over recent decades, and by introduction of genomic technology these are being enhanced. Such continued improvement requires that there be available variation to utilize. The evidence is that little variation has been lost and such rates are indeed sustainable in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 39 publications
(39 reference statements)
1
61
0
3
Order By: Relevance
“…However, despite the success of the past 40 years it has been concluded that investment in family planning is needed to keep up with demand and meet the need of women who are unable to access services (see Population Council). Furthermore in a recent comment in the Lancet (World Abortions 1990to 2014, 2016 it was concluded that additional knowledge, regarding the incidence of induced abortion, is needed to motivate and inform efforts to help women avoid unintended pregnancies and to monitor progress toward that end. It was estimated that abortion rates have declined significantly since 1990 in the developed world, but not in the developing world.…”
Section: Population Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the success of the past 40 years it has been concluded that investment in family planning is needed to keep up with demand and meet the need of women who are unable to access services (see Population Council). Furthermore in a recent comment in the Lancet (World Abortions 1990to 2014, 2016 it was concluded that additional knowledge, regarding the incidence of induced abortion, is needed to motivate and inform efforts to help women avoid unintended pregnancies and to monitor progress toward that end. It was estimated that abortion rates have declined significantly since 1990 in the developed world, but not in the developing world.…”
Section: Population Growthmentioning
confidence: 99%
“…However it is important to realize that a more systems based approach to production will be required, together with the incorporation of new physiological and genetic technologies. Furthermore, despite large genetic improvements in the quantitative traits of growth, production, and efficiency of farmed livestock over recent decades, current evidence suggests that little variation has been lost and that improvements should indeed be sustainable in the future (Hill, 2016).…”
Section: Reproductive Technologies In the 21 St Centurymentioning
confidence: 99%
“…This was highlighted by Swaggerty et al who reported that chicken genotypes which produce high levels of IL‐6, CXCLi2 and CCLi2 in response to Eimeria tenella infection have reduced lesional scores in the caeca. In Europe, although fast‐growing broiler genotypes are commonly used in poultry production, the use of slower‐growing genotypes is beginning to emerge . However, nothing has been reported regarding immune phenotypes in fast and slow growing broilers in response to Eimeria infection, which may determine whether fast or slow growing broilers may differ in their underlying resistance to Eimeria .…”
Section: Introductionmentioning
confidence: 99%
“…In multigeneration selection programmes continued response has been seen, classically for over 100 generations in the Illinois maize kernel content lines, and there have been large and still continuing genetic improvements in livestock populations, notably in broiler chickens (Hill, ). Whilst the “obvious” source of continued response is mutation, some of the additive variation being utilized may have derived from the epistatic to additive conversion of founder and de novo variation.…”
Section: Introductionmentioning
confidence: 99%